Meta Analysis the Effectiveness of Internet-Based Self- Management for Asthma Control Monitoring - dinda khalifatulloh, Bhre diansyah; Tamtomo, Didik Gunawan; Murti, Bhisma (Journal of Health Policy and Management, 2022)
Background: The high incidence and mortality of asthma is caused by a lack of asthma control and the independence of patients and families in doing good self-management. So far, self-management has been carried out in various ways, one of which is using internet-based self-management. The aim of this study was to estimate the effectiveness of Internet-based self-management on asthma control by meta-analysis.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2011-2022 using databases from PubMed, Google Scholar, ProQuest, Science Direct and Scopus. The PICO formula used is P= patients with asthma. I= using internet-based self-management. C= without using internet-based self-management. O= asthma control. Article searches were performed using the keywords “mhealth” OR “mobile health” OR “telemedicine” AND “self management” AND “asthma control” OR “asthma treatment” AND “asthma control”. The inclusion criteria were full paper articles with randomized controlled trial study design, articles using English, the intervention provided was the application of internet-based self-management, and the outcome was asthma control. Based on the database, there were 9 articles that met the inclusion criteria. The analysis was carried out using Revman 5.3 software.Results: A total of 9 articles spread across 4 continents, namely Asia, Europe, Australia, and America. The articles reviewed in the meta-analysis showed that the use of Internet-based self-management in asthmatics was effective in changing asthma control by 1.25 times compared with no Internet-based self-management, and was statistically significant (OR= 1.25; 95% CI= 1.09 to 1.44; p= 0.002).Conclusion: Internet-based self-management is effective in improving asthma control compared to no Internet-based self-management.Keywords: asthma control, internet-based self-management, asthma patientsCorrespondence: Bhre Diansyah Dinda Khalifatulloh. Masters Program in Public Health, universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: bhrediansyah98@gmail.com. Mobile: +6287708465646Journal of Health Policy and Management (2002), 07(02): 94-102https://doi.org/10.26911/thejhpm.2022.07.02.01